Perinatal Risk Factors for Mild Motor Disability - Hands, B.; Kendall, Garth; Larkin, D.; Parker, H. (Routledge, 2009)
The aetiology of mild motor disability (MMD) is a complex issue and as yet is poorly understood. The aim of this study was to identify the prevalence of perinatal risk factors in a cohort of 10-year-old boys and girls with (n = 362) and without (n = 1193) MMD. Among the males with MMD there was a higher prevalence of postpartum haemorrhage, caesarean section, low birth weight and stressful first year of life. Among the females with MMD, there was a higher prevalence of essential hypertension, anaemia and threatened pre-term. Multivariable logistic regression revealed gender(male), anaemia, threatened pre-term birth (if female) and hypertension (if female) weakly explained MMD at 10 years. These results underscore the importance of considering gender differences in order to better understand the multiple influences on motor development.